Woman representative in Divorce: An analysis form Syafi’iyyah Fiqh - Karimuddin Abdullah Lawang; Rika Sasralina; Darwin Sagala; J Jalaluddin; Titin Samsudin (CV. Media Digital Publikasi Indonesia, 2023)
The divorce phenomenon that occurs in society is a husband who assigns his wife the authority to file for divorce, giving up his right to file for divorce himself. Moving past these issues, the author is interested in learning more about the legality of a divorce from a husband to his wife based on the legal foundation of fiqh al-syafi’iyyah. The writers’ method of inquiry is descriptive qualitative research with a normative perspective. The study’s findings indicated that the legality of divorce on a wife according to fiqh scholars al-syafi’īyyah is valid and the fall of divorce is because there is a need (hajat) and this opinion is a strong opinion to practice. This is different from the case of a husband delegating his wife’s divorce to another woman. There is a difference in the opinion of scholars, some fiqh al-Syafi’iyyah scholars say it is legal, some others argue that it is illegal on the grounds that there is no intention and women also cannot accept representation.